Hubungan Pengetahuan dan Sikap terhadap Perilaku Higiene Sanitasi Penjamah Makanan di Warung Makan Sekitar Universitas Muhadi Setiabudi - Anggi Citra Suryani; Rifatul Masrikhiyah; Sulasyi Setyaningsih (Jurnal Ilmu Kesehatan dan Gizi, 2025)
The knowledge and attitudes of food handlers are pivotal in fostering proper hygiene practices; however, not all individuals grasp and implement the requisite standards. The aim of this study is to examine the correlation between knowledge and attitudes regarding the behavior of food handlers in the context of hygiene and sanitation practices at Muhadi Setiabudi University. The study uses an observational methods. The research design used was cross-sectional in nature. A total of 59 food handlers were selected for the study, all of whom fulfilled the established criteria. The sampling method employed was purposive sampling. The findings indicate that 26 individuals, representing 44.1%, demonstrated a commendable level of knowledge, while 33 individuals, or 55.9%, exhibited a lack of knowledge. Furthermore, 54 individuals, accounting for 91.5%, displayed a positive attitude, in contrast to 5 individuals, or 8.5%, who showed a negative attitude. Additionally, 26 individuals, corresponding to 44.1%, engaged in commendable behavior, whereas 33 individuals, or 55.9%, were characterized by poor behavior. The Chi-square test revealed a relationship between knowledge and behavior, indicated by p > 0.05 (p = 0.809), and between attitude and behavior, evidenced by p < 0.05 (p = 0.848). No correlation exists between knowledge and attitudes regarding food handler behavior.